Moxifloxacin‐induced QTc interval prolongations in healthy male Japanese and Caucasian volunteers: a direct comparison in a thorough QT study. (2nd July 2015) - Morganroth, Joel; Wang, Yaning; Thorn, Michael; Kumagai, Yuji; Harris, Stuart; Stockbridge, Norman; Kleiman, Robert; Shah, Rashmi
<x xml:space="preserve">Abstract</x> Aim We investigated whether moxifloxacin‐induced QTc prolongations in Japanese and Caucasian healthy male volunteers were significantly different. Methods A two period, randomized, crossover, ICH‐E14‐compliant thorough QT (TQT) study compared placebo‐corrected changes in QTc interval from baseline (ΔΔQTcF) and concentration–effect relationships following administration of placebo and 400 mg moxifloxacin to 40 healthy male volunteers from each ethnic population. The point estimates of ΔΔQTcF for each population, and the difference between the two, were calculated at a geometric mean Cmax of moxifloxacin using a linear mixed effects model. The concentration–effect slopes of the two populations were also compared. Equivalence was concluded if the two‐sided 90% confidence interval of the difference in ΔΔQTcF was contained within −5 ms to +5 ms limits and the ratio of the slopes was between 0.5 and 2. Results There were no statistically significant differences between the two populations studied, Japanese vs. Caucasians, respectively, for moxifloxacin Cmax (3.27 ± 0.6 vs. 2.98 ± 0.7 µg ml–1), ΔΔQTcF (9.63 ± 1.15 vs. 11.46 ± 1.19 ms at Cmax of 3.07 µg ml–1) and concentration–response slopes (2.58 ± 0.62 vs. 2.34 ± 0.64 ms per µg ml–1). The difference in the two ΔΔQTcF of −1.8 (90% CI −4.6, 0.9) and the ratio of the two slopes (1.1; 90% CI 0.63, 1.82) were within pre‐specified equivalence limits. Conclusions Moxifloxacin‐induced QTc prolongations did not differ significantly between the Japanese and Caucasian subjects. However, before our findings are more widely generalized, further studies in other populations and with other QT‐prolonging drugs are needed to clarify whether inter‐ethnic differences in QT sensitivity exist and whether ethnicity of the study population may affect the outcome of a TQT study.